The impact of structural and technological change according to Saudi Vision 2030 on the performance of human resources, a case study of the Saudi Electricity Company - Abdelfattah Allaoui; Abdullah Saleh Al-Najrani (Journal of North African Economies, 2025)
This study aims to identify the impact of both structural and technological changes on the performance of human resources in the Saudi Electricity Company. After presenting the theoretical side of the study and identifying its variables, a questionnaire containing 40 words is designed, trying to measure the relationship between the variables and the possibility of the impact of both structural and technological change on the performance of the employees in the company subject of this study. The results showed that the variable of technological change is the most statistically significant because the corresponding Beta value of this variable is equal to 0.377 and is therefore statistically significant at a level less than (0.05). This variable is followed by the change variable which includes the organizational structure where the value of (Beta) corresponding to this variable is equal to 0.219 and is statistically significant at a level less than (0.05).